Cutaneous Lymphoma in a Tertiary Skin Hospital and Referral Centre in Nepal - Adhikari, Ram Chandra; Shah, Mahesh; Kempf, Werner; Jha, Anil Kumar (Journal of Nepal Health Research Council, 2024)
Background: Primary cutaneous lymphomas are a distinct group of rare lymphoid neoplasms with absence of extracutaneous lymphomas at the time of presentation. They are rare in Nepal and no data on cutaneous lymphoma have been published from this country till date.Methods: This retrospective study included 15 cases of cutaneous lymphomas retrieved from the records of department of Dermatopathology, DI Skin Hospital and Referral Centre, Bansbari, Kathmandu, Nepal. Patients were diagnosed according to the current WHO classification for cutaneous lymphoma. Results: A total of 15 cases were studied with median age of 45 years (range: 22 to 81 years) and male to female ratio of 1.5:1. Primary cutaneous lymphomas constituted 13 cases out of 15 and the most common type of cutaneous lymphoma was mycosis fungoides and variants 5 (33%), followed by CD30 positive primary cutaneous anaplastic large cell lymphoma constituting 2 (13%). T-cell cutaneous lymphoma constituted 13 (87%) and B-cell cutaneous lymphoma 2 (13%). Conclusions: Cutaneous T-cell lymphomas were more frequent than cutaneous B-cell lymphomas in Nepalese patients. Mycosis fungoides and variants are commonest type of primary cutaneous lymphomas. Keywords: Histopathology; mycosis fungoides; primary cutaneous t-cell lymphoma; WHO classification.